The Use of YouTube As A Medium for Teaching English Writing Skill During Covid-19 Pandemic - Aenun Mutoharoh; Alisa Zumrotul ‘Ulya; Euis Nawangsari; Salamatun Riska Fatin; Maulana Mualim (Tarling : Journal of Language Education, 2022)
A popular video sharing site, YouTube, could be used as an alternative teaching medium in online learning activities during the COVID-19 pandemic. It is useful to help students to keep on learning and get materials well in the difficult circumstance caused by the pandemic. This study aims to describe how Youtube is used as a learning medium in English teaching, especially the writing skill at MTs Ma'aarif NU 01 Kemranjen during the COVID-19 pandemic. This study uses a qualitative approach. Data are collected through the triangulation of interview, observation, and documentation. The data are then analysed by applying Miles and Huberman’s (1994) model of data reduction, data display, and verification. The results of this study reveal that Youtube is seen to be a good learning medium to cope with the learning difficulties in the unprecedented Covid-19 crisis. The asynchronous nature of the Youtube videos enabled students to repeat the video as much as they want to. The implementation of Youtube in online learning was done in three stages: 1) preparation, the teacher makes and uploads the videos; 2) implementation, the teacher shares the link and provides brief explanation on WhatsApp; and 3) evaluation, the teacher gives quizzes to ensure that the materials are well-received. Meanwhile, the obstacles in the implementation are poor Intenet network, insufficient facilities, and unmotivated students. The pedagogical implication from this study is that Youtube is a good fit for online learning, it is highly recommended for teaching during the pandemic.